Persilangan Genotipe-Genotipe Kedelai (Glycine max L. Merrill.) Hasil Seleksi pada Tanah Salin dengan Tetua Betina Varietas Anjasmoro - Maria Sitepu; Rosmayati Rosmayati; Mbue kata Bangun (Jurnal Agroekoteknologi, 2015)
The research aimed is to determine soybean varieties toleran salinity through crossing of numbers soybean derivative varieties in the land of salinity with Anjasmoro varieties as female parent. Theresearch was carried out in plastic  house Agriculture’s Faculty of North Sumatera  University,Medan, In Indonesia with height ± 25 m above of surface of the sea.  Which was held in Mei toAugust. The research used Completely Randomized Design with five combination crossing with tenreplicanst to observe the result of crossing that is AnjasmorxN1, AnjasmorxN,AnjasmoroxN4 and AnjasmoroxN. A result of the reset shows that the result of crossing, an age ofparameter to get a flowers, a percentage of crossing success, an age of harvest, a numbers of podwhich contains 3 seeds and it is significant different but it is not significant to the number offlowers and weight for 10 seeds. 5Key words : crossing, genotype soybean, saline soil.2, AnjasmoroxN3